Carloticola gen. n. e. Carloticola trichura sp. n. da Argentina (Apoidea, Megachilidae, Anthidiinae) - Moure, Jesús Santiago; Urban, Danúncia (Acta Biológica Paranaense, 1990)
Carloticola gen. n. e. Carloticola trichura sp. n. da Argentina (Apoidea, Megachilidae, Anthidiinae)